Biophilic Design in Bedrooms that Supports the Process of Holistic Art Therapy - Octavianus Cahyono Priyanto (Bina Nusantara University, 2025)
Emotional health and psychological well-being are essential considerations in the design of private spaces, particularly bedrooms. A bedroom serves not only as a place for rest but also as a space for deep personal expression. This study explores the integration of biophilic design elements in bedrooms as a strategy to support holistic art therapy focused on emotional healing. Art therapy is viewed as a holistic approach that utilizes creative expression as a means of psychological recovery. In this context, biophilic design contributes by creating a natural and calming atmosphere that fosters emotional balance. This research employs a qualitative approach through literature review and interior design analysis, incorporating natural elements such as daylight, plants, natural textures, and organic colors. The findings indicate that integrating biophilic design into bedrooms can create environments that effectively support art therapy activities, enhance relaxation, and strengthen the emotional connection between individuals and their personal space. These insights open new opportunities for developing interior design strategies that promote psychological healing and holistic well-being through a more emotionally responsive design approach.